MODEL SEBARAN SPASIAL KUALITAS AIR TANAH UNTUK AIR MINUM DI KECAMATAN JOMBANG KABUPATEN JOMBANG - Siswoyo, Hari; Harisuseno, Donny; Taufiq, Mohammad; Azhar, Rifqi Fajar (JST (Jurnal Sains dan Teknologi), 2021)
Most of the population in the Jombang District area uses groundwater from dug wells and bor wells to meet their daily water needs. The quality of water from these wells was not always well controlled. The purpose of this research was to assess the quality of groundwater for drinking water and map its distribution patterns in the research location. The type of this research was development research with a descriptive research design. The groundwater quality index value for drinking water was determined based on the water quality index model and then mapped its distribution spatially in the study area. The spatial distribution of groundwater quality for drinking water in the study area, both during the rainy season and the dry season was dominated by areas with good and very good groundwater quality. The spatial distribution model of groundwater quality can be used as an indicator to assess the appropriateness of groundwater quality for drinking water in the research location.